Effects of Transcranial Direct Current Stimulation, Transcranial Pulsed Current Stimulation, and Their Combination on Brain Oscillations in Patients with Chronic Visceral Pain: A Pilot Crossover Randomized Controlled Study - Thibaut, Aurore; Russo, Cristina; Hurtado-Puerto, Aura Maria; Morales-Quezada, Jorge Leon; Deitos, Alícia; Petrozza, John Christopher; Freedman, Steven; Fregni, Felipe (Frontiers in Neurology, 2017)
Objective: Chronic Visceral Pain (CVP) syndromes are persistently painful disorders with a remarkable lack of effective treatment options. This study aimed at evaluating the effects of different neuromodulation techniques in patients with CVP on cortical activity, through electreocephalography (EEG) and on pain perception, through clinical tests. Methods: In this pilot crossover randomized controlled study, adults with chronic visceral pain (>3months) received 4 interventions in a randomized order: 1. active transcranial Pulsed Current Stimulation (tPCS) and active transcranial Direct Current Stimulation (tDCS) combined, 2. active tPCS and sham tDCS, 3. Active tDCS and sham tPCS and 4. Sham tPCS and sham tDCS. Before and after each intervention resting state Quantitative Electroencephalography (qEEG) and pain assessments were performed. Results were compared to a cohort of 47 healthy controls. Results: We enrolled six patients with CVP for a total of 21 visits completed. Compared to healthy participants, patients with CVP showed altered cortical activity characterized by increased power in theta, alpha and beta bands, and a significant reduction in the alpha/beta ratio. Regarding tES, the combination of tDCS with tPCS had no effect on power in any of the bandwidths, nor brain regions. Comparing tPCS with tDCS alone, we found that tPCS induced higher increase in power within the theta and alpha bandwidths. Conclusion: This study confirms that patients with CVP present abnormal EEG-indexed cortical activity compared to healthy controls. Moreover, we showed that combining two types of neurostimulation techniques had no effect, whereas, the two interventions, when applied individually, have different neural signatures.